Clinical and Prognostic Impact of the Warburg Effect in Esophageal Carcinoma: Monocarboxylate Transporters as Candidates for Therapeutic Targeting - Afonso, Julieta (2023)
Introduction: Esophageal cancer (EC) seems to display increased glycolytic activity, but clinical studies on the expression/prognostic significance of glycometabolism-related proteins, as well as functional assays, are missing. Methods: Expression of 10 glycolytic biomarkers was evaluated by immunohistochemistry in tissue sections from 95 patients. Two esophageal squamous cell carcinoma (ESCC) cell lines were used to assess the effect of monocarboxylate transporter (MCT) downregulation on cell viability and extracellular lactate/glucose accumulation. Results: Expression of MCT1, MCT4, CD147, and GLUT1 was significantly associated with an ESCC histopathology, while a poor clinicopathological profile was seen in GLUT1- and LDHA-positive EC cases. In the ESCC group, MCT1 immunoreactivity is associated with high TNM stage and metastasis. The 3-year overall survival (OS) rate was significantly influenced by MCT4 and CAIX positivity and HKII negativity. Those biomarkers were considered independent prognostic factors of OS in multivariate analysis. Dual inhibition of MCT1/4 expression decreased cell viability and extracellular lactate accumulation in ESCC cells. Conclusion: Elevated glycolytic rates correlate with a poor clinicopathological profile in EC patients. MCT4 and CAIX positivity independently predict a worse prognosis. Due to the lack of information on treatment modalities, we could not further infer the role of these biomarkers in predicting response to therapy, which needs to be assessed in future studies. In addition, MCT1/4 targeting should be performed both in vitroand in vivoto further explore its impact on tumor growth and response to classical therapies. HKII expression and function, particularly in the tumor stroma, should be investigated.